(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
Classroom situations have globally shifted from monolingual to multilingual perspectives due to globalisation and movement across the world. This has raised awareness of the fluid and porous nature of linguistic boundaries between and across nations. The situation necessitates adoption of new approaches in teaching and learning in multilingual classroom contexts. Translanguaging pedagogy is one of the approaches that allows concurrent use of several languages in multilingual classrooms. This article investigates how teachers could use translanguaging to develop reading comprehension in bi/multilingual classroom contexts. The participants were four Grade 5 teachers, two of whom teach English and two teaching Sesotho. The study employed a quasiexperimental design and used pre- and post-tests on reading comprehension, in both English and Sesotho. The experimental group was subjected to a translanguaging intervention between the pre- and post-tests periods to determine the impact of the intervention. The results showed that the experimental group outperformed the control group confirming translanguaging as a pedagogy that could improve learners’ reading comprehension. The study concludes and recommends translanguaging as relevant in assisting teachers’ use of learners’ linguistic repertoires to improve reading comprehension in multilingual classroom contexts.